Review—Light Emission from Thin Film Solar Cell Materials: An Emerging Infrared and Visible Light Emitter. (1st January 2018) - Kanemitsu, Yoshihiko; Okano, Makoto; Phuong, Le Quang; Yamada, Yasuhiro
Abstract : In the last decade, there have been extensive studies on fabrication and physics of thin-film solar cell materials and devices. Many high-efficiency solar cell devices have been developed, and the knowledge gained in these studies can be used advantageously to produce bright light-emitting devices. In this review, we summarize recent luminescence spectroscopic studies on new solar-cell materials and discuss their photocarrier dynamics with respect to efficient light emission.